PENGARUH FAKTOR PSIKOLOGIS TERHADAP KEPUTUSAN WISATAWAN DALAM MEMILIH WISATA ZIARAH (Studi Pada Pengunjung Wisata Ziarah Makam Sunan Bonang di Tuban) - Tartar, Qibbar (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study aims to determine the influence of psychological factors which consist of motivation, perception, learning, beliefs and attitudes towards tourist decision in choosing a tourist attraction pilgrimage (pilgrimage tourism studies in the tomb of Sunan Bonang in Tuban district). The study used a sample of 100 respondents in the capture of polulasi visitors who come to the grave of Sunan Bonang, Tuban.. analysis using multiple linear regression Â analysis. Based on the results of this study show the influence of motivation, perception, learning, beliefs and attitudes of 57.1% against the decision of visiting tourists. Based on F test showed that motivation, perception, learning, beliefs and attitudes simultaneous influence on the decision to visit. Based on t test showed that motivation, perception and attitude except keprcayaan learning turns partial effect to the decision to visit, while the beliefs and attitudes of the dominant influence on decisions visiting tourists.Keywords: Psychological factors, motivation, perception, learning, beliefs and attitudes,